2019
DOI: 10.3390/polym11020342
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Structure and Thermal Property of Starch-Based Nanocomposites with Different Amylose/Amylopectin Ratio

Abstract: Starch-based materials with reinforced properties were considered as one of the most promising materials to replace the petro-based packaging products, and actually, the molecular structures of starch usually determined the structures and properties of end-used starchy products. Here, starch-based nanocomposites were fabricated by starch esters derived from native starches with different amylose contents and organically modified montmorillonite (OMMT). The fractured surface under scanning electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Studies have shown that high amylose content will hinder acid hydrolysis to a certain extent, and that starches with lower amylose content have smaller SNC sizes and higher crystallinity. Waxy potato starch (WPS) contains 99% amylopectin and is very suitable for producing SNCs [ 22 , 23 , 24 ]. There are many reports on starch modification, but few reports on the modification of waxy potato starch with sodium hexametaphosphate (SHMP) and vinyl acetate (VAC) and the preparation of SNCs from modified starch.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that high amylose content will hinder acid hydrolysis to a certain extent, and that starches with lower amylose content have smaller SNC sizes and higher crystallinity. Waxy potato starch (WPS) contains 99% amylopectin and is very suitable for producing SNCs [ 22 , 23 , 24 ]. There are many reports on starch modification, but few reports on the modification of waxy potato starch with sodium hexametaphosphate (SHMP) and vinyl acetate (VAC) and the preparation of SNCs from modified starch.…”
Section: Introductionmentioning
confidence: 99%
“…When the amount of CMC added was more than .4 g, the water contact angle of the CS/CMC composite film was greater than that of the CA/CMC composite film. The analysis showed that when CMC was added in small amounts, the hydrophilicity of their composite films was better because of the higher content of amylopectin in the films (Zhang et al, 2019). When more CMC was added, new hydrogen bonds were formed between CMC and CA, resulting in a tighter structure of the composite film and the destruction of the original structure; this exposed the hydrophobic groups to the surface of the film and caused the surface to be less hydrophilic (Jose et al, 2012).…”
Section: Stability Analysismentioning
confidence: 99%
“…It accumulates as granules in plant cells and these granules have crystalline and amorphous regions. They are composed of amylose and amylopectin, and higher levels of amylose are desirable as this compound contributes to the film resistance, in addition to reducing the water solubility [ 40 ]. Commercially available starch is obtained mainly from potatoes and other sources include corn, rice and wheat.…”
Section: Sustainable Innovations In the Cosmetic Industrymentioning
confidence: 99%
“…PHAs are polyesters synthesized intracellularly by some micro-organisms, such as carbon, energy and fatty acids reserves, metabolized under stress conditions. These polyesters are biodegradable and originate from renewable carbon sources [ 39 , 40 ]. With regard to large-scale production, PHAs are often overlooked, given the high cost of acquiring expensive fermentation carbon sources, which account for approximately 40% of total PHA production costs [ 47 , 48 ].…”
Section: Sustainable Innovations In the Cosmetic Industrymentioning
confidence: 99%